The impact of dementia on family carers using the ICF framework - Grigoriou, Stavroulla (Department of Rehabilitation Sciences, Faculty of Health Sciences, Cyprus University of Technology, 2021)
Dementia is defined as a disorder, that describes a series of symptoms related to memory loss, functioning deficit, and behavioural problems. Due to its progressive nature, dementia is a significant reason for disability and dependency among elderly people. This has a huge impact on people with dementia (PWD) as well as their carers. The aim of the current study is to describe the impact of dementia on family carers using the International Classification of Functioning, Disability and Health (ICF) framework as a model to interpret the findings. This study followed a multi-method design, using qualitative and quantitative data. A total of one hundred dementia carers participated in this study. All participants completed an online survey in Google Forms. The results from the questionnaire were mapped onto the ICF framework to determine the impact of dementia on carers’ lives. The results, according to the ICF, revealed that, on the whole, dementia carers experience negative changes to body function, activities and participation as a result of caring for PWD. Furthermore, dementia carers attribute the detrimental effects on their health and well-being to dementia. Taking into consideration the results of this study, dementia carers experience changes to their daily functioning as a result of the cared one’s health condition. This has been described as carer’s “third- party disability” in the literature.
Keywords: Dementia; Carers; ICF; Third-party disability; Impact